2019
DOI: 10.1016/j.jallcom.2018.09.262
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of YAlO3/NbC heterogeneous nucleation interface: First principles calculation and experimental research

Abstract: Structure and properties of YAlO3/NbC heterogeneous nucleation interface: First principles calculation and experimental research http://researchonline.ljmu.ac.uk/id/eprint/9834/ Article LJMU has developed LJMU Research Online for users to access the research output of the University more effectively. , Q (2018) Structure and properties of YAlO3/NbC heterogeneous nucleation interface: First principles calculation and experimental research. Journal of Alloys and Compounds, 773. pp. AbstractThe characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Table 2 shows the interfacial energy of four different stacking models after total relaxation. In general, the smaller the interfacial energy, the more stable the interfacial structure and the better the wettability [34]. As can be seen from the table, compared with other interfaces, the Long bridge interface has the lowest interface energy of 1.083 J/m 2 .…”
Section: Aucu(200) Surmentioning
confidence: 89%
“…Table 2 shows the interfacial energy of four different stacking models after total relaxation. In general, the smaller the interfacial energy, the more stable the interfacial structure and the better the wettability [34]. As can be seen from the table, compared with other interfaces, the Long bridge interface has the lowest interface energy of 1.083 J/m 2 .…”
Section: Aucu(200) Surmentioning
confidence: 89%
“…Therefore, NbC (111) and TiC (111) with thicknesses larger than thirteen atomic layers were chosen to construct the interfaces in the following calculations. The surface energies of NbC and TiC were calculated using the method of Shi et al [16,31], and the results are shown in Figure 1a,b respectively. It is found that the surface energies of Nbterminated and C-terminated NbC (111) are 1.75-2.88 and 5.70-6.83 J/m 2 , respectively.…”
Section: Surface Properties Of Nbc and Ticmentioning
confidence: 99%
“…One available and effective method of studying an interface is first-principles calculation based on density functional theory (DFT), which has been extensively employed to investigate the micro-characterization of surfaces and interfaces at the atomic scale [14,15]. For example, a previous report revealed the atomic-scale characteristics of the YAlO 3 /NbC interface by DFT calculation and proved the occurrence of NbC growth encircling YAlO 3 by their experimental method [16]. Additionally, the first-principles calculation was used to investigate the electronic and atomic properties of the Al/NbB 2 interface, and the heterogeneous nucleation mechanism of α-Al grains on NbB 2 particles was determined [17].…”
Section: Introductionmentioning
confidence: 99%
“…NbC ceramic particles possess a high melting point (3490 °C), high hardness (HV 2400), a high elasticity modulus (338.5 GPa), a low coefficient of linear expansion (6.5 × 10 −6 K −1 ), and high chemical and physical stability . The melting point, hardness, elasticity modulus, and coefficient of thermal expansion of NbB 2 are 3050 °C, 2600 kg mm −2 , 445 GPa, and 7.44 × 10 −6 K −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%